2011
DOI: 10.1116/1.3633691
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy measurement of the Schottky barrier at the SiC(N)/Cu interface

Abstract: Electrical leakage in low-k dielectric/Cu interconnects is a continuing reliability concern for advanced <22 nm technologies. One leakage mechanism deserving increased attention is electron transport across the Cu/dielectric capping layer interface. The Schottky barrier formed at this interface is an important parameter for understanding charge transport across this interface. In this report, we have utilized x-ray photoelectron spectroscopy to investigate the Schottky barrier formed at the interface be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 84 publications
2
49
0
Order By: Relevance
“…For comparison, SiO 2 and SiN:H films were grown on 300 mm diameter silicon (001) substrates via thermal oxidation and PECVD, respectively. 125,126 We do note that the above mentioned film thicknesses are significantly higher than those typically utilized in traditional Si CMOS high-k dielectric applications where thicknesses of <10 nm are more common. [2][3][4][5][6][7][8] However, many of the applications involving these materials as diffusion barriers, 27,31,127 nano-resonators, 80,81 and piezoelectric transducers 43,87 can require significantly higher thicknesses of 20-1000 nm.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, SiO 2 and SiN:H films were grown on 300 mm diameter silicon (001) substrates via thermal oxidation and PECVD, respectively. 125,126 We do note that the above mentioned film thicknesses are significantly higher than those typically utilized in traditional Si CMOS high-k dielectric applications where thicknesses of <10 nm are more common. [2][3][4][5][6][7][8] However, many of the applications involving these materials as diffusion barriers, 27,31,127 nano-resonators, 80,81 and piezoelectric transducers 43,87 can require significantly higher thicknesses of 20-1000 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[239][240][241][242] For low-k DB materials, there has been some concern regarding what UV curing will do the material properties of the DB given the smaller band-gap and larger absorption coefficient in the UV-VUV spectrum for these materials. 50,243 While exhaustive studies have not been reported, several studies of PECVD a-SiN:H have shown that UV curing leads to hydrogen loss, densification and a decrease in compressive stress (or increase in tensile stress). [244][245][246] Additional studies have shown that UV curing can also result in an increase in paramagnetic defect densities and leakage currents.…”
Section: -122mentioning
confidence: 99%
“…This can be a challenging and conflicting requirement for a-SiN:H and aSiCN:H DB materials that are typically deposited using NH 3 and/or silazane precursors and can contain significant amounts of residual amines after deposition. [41][42][43][44][45][46][47][48][49][50][51] The no amines requirement can also be a challenge for a-SiC:H and a-SiCO:H DB materials that do not incorporate nitrogen in the deposition process, but that may utilize an NH 3 plasma pre-treatment to improve adhesion of the DB to the underlying Cu and low-k ILD surfaces.…”
Section: 318mentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS measurements were performed after ex-situ transfer to a VG Theta 300 XPS system having a hemispherical analyzer and a monochromated Al anode X-ray source (1486.6 eV). 34 Removal of ex-situ surface contamination and depth profiling was achieved using a 2 keV Ar + ion sputtering beam. A pass energy of 20 eV was utilized for collecting high resolution scans of the B1s, N1s, C1s, and O1s core levels as the Ar + beam sputtered through a portion of the film.…”
Section: N3123mentioning
confidence: 99%